2016
DOI: 10.14814/phy2.12898
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and activity-dependent catecholamine release in rat adrenal medulla under native neuronal stimulation

Abstract: Neuroendocrine chromaffin cells of the adrenal medulla in rat receive excitatory synaptic input through anterior and posterior divisions of the sympathetic splanchnic nerve. Upon synaptic stimulation, the adrenal medulla releases the catecholamines, epinephrine, and norepinephrine into the suprarenal vein for circulation throughout the body. Under sympathetic tone, catecholamine release is modest. However, upon activation of the sympathoadrenal stress reflex, and increased splanchnic firing, adrenal catecholam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Regarding E and NE secretion, we observed a bias toward a shift from central to peripheral E and NE release upon ACh challenges, suggesting that peripheral and central CA secretion might be differentially regulated. Along the same line, an attempt to answer this thorny issue has been recently reported using an elegant ex vivo spinal–splanchnic nerve–adrenal preparation ( 85 ). The authors showed that upon robust splanchnic nerve stimulation, E seems to be preferentially released from the periphery and NE secreted from the center of the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding E and NE secretion, we observed a bias toward a shift from central to peripheral E and NE release upon ACh challenges, suggesting that peripheral and central CA secretion might be differentially regulated. Along the same line, an attempt to answer this thorny issue has been recently reported using an elegant ex vivo spinal–splanchnic nerve–adrenal preparation ( 85 ). The authors showed that upon robust splanchnic nerve stimulation, E seems to be preferentially released from the periphery and NE secreted from the center of the medulla.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in firing rate, in turn, may reflect the changing demands placed on them as effectors of the sympathetic stress response (39). In experimental paradigms mimicking strong sympathetic activation of chromaffin cell secretion, splanchnic input has been stimulated at rates that ranged from 10 -20 Hz (30,38,40). We sought to determine whether the splanchnic synapse fa- cilitates even at these high firing rates, or whether it might undergo depression.…”
Section: R a F Tmentioning
confidence: 99%
“…Once isolated from animals or differentiated from stem cells, both AMCCs and cultured adrenal slices lack neural regulation. Both in vivo and ex vivo models have been used to investigate the SAM axis, and together have helped establish our current understanding of neurogenic control of CAT release (26). Due to the confounding impact of autonomic regulation and other feedback mechanisms, however, in vivo approaches are ill-suited for developing a comprehensive understanding of the cellular mechanisms regulating CAT release.…”
Section: Introductionmentioning
confidence: 99%